PHONETIC STYLISTIC DEVICES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article deals with the analysis of phonetic stylistic devices and expressive means in the works of poets. Examples from poetry are given in this research work and they are of great importance for learning stylistics.